Incongruity in Interaction: A Muysken-Based Typological Analysis of Code-Mixing as a Humorous Device in Lapor Pak! - Hilya Fitriatuz Zahra (Pustaka Digital Indonesia, 2026)
In contemporary Indonesian media, code-mixing has become an increasingly prominent linguistic practice, particularly in entertainment programs where language is creatively manipulated to engage audiences. This study aims to analyze the forms and social functions of Indonesian–English code-mixing used by comedians in the television program Lapor Pak!, as well as to examine how these linguistic structures are strategically employed as instruments for creating humor. The research employs a qualitative descriptive method, with data sourced from three selected videos on the @7comedy YouTube channel through observation and note-taking techniques. The analysis is grounded in Pieter Muysken’s typology of code-mixing, Hoffman’s and Wardhaugh’s sociolinguistic theories, and Salvatore Attardo’s Incongruity Theory. The findings reveal that code-mixing in the program is dominated by the insertion type, followed by alternation and congruent lexicalization. These linguistic choices serve various sociolinguistic functions, including affective functions to express emotion, phatic functions to maintain social interaction, and the use of technical terms to build specific character personas. Comedians strategically use English not only as a communication tool but also as a comedic instrument. Humor arises from the incongruity between the formal or serious nature of the English terms and the absurd or trivial context of the comedic sketches. Overall, this study demonstrates that Indonesian English code-mixing in Lapor Pak! is not a random linguistic practice but a deliberate comedic strategy that simultaneously constructs humor, negotiates social identity, and reflects contemporary sociolinguistic dynamics.